2003
DOI: 10.1152/ajpheart.00207.2003
|View full text |Cite
|
Sign up to set email alerts
|

Targeted deletion of MMP-2 attenuates early LV rupture and late remodeling after experimental myocardial infarction

Abstract: . Targeted deletion of MMP-2 attenuates early LV rupture and late remodeling after experimental myocardial infarction. Am J Physiol Heart Circ Physiol 285: H1229-H1235, 2003. First published May 29, 2003 10.1152/ ajpheart.00207.2003.-Matrix metalloproteinase-2 (MMP-2) is prominently overexpressed both after myocardial infarction (MI) and in heart failure. However, its pathophysiological significance in these conditions is still unclear. We thus examined the effects of targeted deletion of MMP-2 on post-MI lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
235
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(253 citation statements)
references
References 28 publications
15
235
1
2
Order By: Relevance
“…[30][31][32] Recent studies using MMP knockout mice or administration of MMP inhibitors have provided insights into the involvement of particular MMP species in unfavorable LV remodeling after MI. [33][34][35][36] In this study, the area of myocardial fibrosis, TGF-b1 protein level, CTGF and OPN mRNA levels, and the activity of MMP-2 and MMP-9 were all increased in the noninfarcted myocardium 7 days after induction of MI compared with sham-operated rats. Importantly, Telmisartan ameliorated these unfavorable changes.…”
Section: Discussionmentioning
confidence: 47%
“…[30][31][32] Recent studies using MMP knockout mice or administration of MMP inhibitors have provided insights into the involvement of particular MMP species in unfavorable LV remodeling after MI. [33][34][35][36] In this study, the area of myocardial fibrosis, TGF-b1 protein level, CTGF and OPN mRNA levels, and the activity of MMP-2 and MMP-9 were all increased in the noninfarcted myocardium 7 days after induction of MI compared with sham-operated rats. Importantly, Telmisartan ameliorated these unfavorable changes.…”
Section: Discussionmentioning
confidence: 47%
“…In this study, we showed increased induction of gelatinase activity (i.e., of MMP-9 and MMP-2) in the noninfarcted myocardium 7 days after induction of MI. Recent studies using transgenic mouse models of MMP deletion and MMP inhibitor have provided further insight into the involvement of particular MMP species in LV remodeling after MI (5,11,25). These data suggest the importance of gelatinases in the development of LV remodeling.…”
Section: Diastolic Dysfunction and Nf-b Inhibitionmentioning
confidence: 92%
“…Following myocardial infarction, catastrophic mechanical complications, such as cardiac rupture (129), are associated with accentuated matrix degradation or perturbed deposition of new structural matrix (130). These can be treated through application of a patch containing ECM proteins to restore the structural integrity of the ventricle (131).…”
Section: Therapeutic Ecm Targeting In Injured and Remodeling Myocardiummentioning
confidence: 99%